2016
DOI: 10.2147/dmso.s87873
|View full text |Cite
|
Sign up to set email alerts
|

rDNA insulin glargine U300 – a critical appraisal

Abstract: BackgroundAs the first once-daily basal insulin analog, insulin glargine 100 U/mL (Gla-100; Lantus®) rapidly evolved into the most commonly prescribed insulin therapy worldwide. However, this insulin has clinical limitations. The approval of new basal insulin analogs in 2015 has already started to alter the prescribing landscape.ObjectiveTo review the available evidence on the clinical efficacy and safety of a more concentrated insulin glargine (recombinant DNA origin) injection 300 U/mL (Gla-300) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…As T2DM progresses, the need of patients for glycemic control gradually increases, and most patients eventually require insulin for glycemic control ( 44 ). Glargine is the first long-acting basal analog of insulin with superior glucose-lowering effects ( 45 , 46 ). But unfortunately, it increases the risk of weight gain and hypoglycemia ( 47 ), which are risk factors of T2DM, so the guidelines do not recommend insulin for all patients with T2DM ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…As T2DM progresses, the need of patients for glycemic control gradually increases, and most patients eventually require insulin for glycemic control ( 44 ). Glargine is the first long-acting basal analog of insulin with superior glucose-lowering effects ( 45 , 46 ). But unfortunately, it increases the risk of weight gain and hypoglycemia ( 47 ), which are risk factors of T2DM, so the guidelines do not recommend insulin for all patients with T2DM ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmed or severe nocturnal hypoglycemia was significantly lower in 1 study (16) but not in other shorter trials (15). Insulin glargine U-300 may require a higher dose than insulin glargine U-100 and may result in less weight gain (15,17).…”
Section: Basal Insulin and Basal-bolus Injection Therapymentioning
confidence: 90%
“…A pertinent observation was of a difference in dose requirement of basal insulin that was both statistically and clinically significant and in favour of Gla‐100 over Gla‐300, for both the T1D and T2D populations. Both RCTs and real‐world evidence (RWE) studies have shown that the basal insulin doses for Gla‐300 needed to achieve equivalent glycaemic control were 10%‐20% higher than for Gla‐100 in T1D and T2D patients 8,12,18,21,26‐29 . This difference is more pronounced in insulin‐naïve populations treated with Gla‐300 or Gla‐100.…”
Section: Discussionmentioning
confidence: 99%